2013
DOI: 10.4103/0259-1162.118947
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative conditions and quality of postoperative analgesia after adding dexmedetomidine to epidural bupivacaine and fentanyl in elective cesarean section using combined spinal-epidural anesthesia

Abstract: This study was designed to evaluate the effect of adding dexmedetomidine to regular mixture of epidural drugs for pregnant women undergoing elective cesarean section with special emphasis on their sedative properties, ability to improve quality of intraoperative, postoperative analgesia, and neonatal outcome.Materials and Methods:Fifty women of ASA physical status I or II at term pregnancy were enrolled randomly to receive plain bupivacaine plus fentanyl (BF Group) or plain bupivacaine plus mixture of fentanyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
2
28
1
1
Order By: Relevance
“…Moreover, shivering, nausea and vomiting were also less in the dexmedetomidine group compared with the morphine group, consistent with other studies. [25][26][27][28] The low incidence of shivering might reflect a decreased shivering threshold and a lower core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, shivering, nausea and vomiting were also less in the dexmedetomidine group compared with the morphine group, consistent with other studies. [25][26][27][28] The low incidence of shivering might reflect a decreased shivering threshold and a lower core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,19 Onset of postoperative pain was significantly early in the group A than group B or group C, with the need for supplementary analgesic in group A. 20 The cardiovascular stability was better in group A and B than group C. Eight patients had bradycardia and six patients had hypotension in group C which was treated with atropine and phenylephrine respectively. A study ZA Zang et al, 21 with low dose epidural dexmeditomidinem i.e.…”
Section: Discussionmentioning
confidence: 96%
“…But it can produce side effects like bradycardia and hypotension in some patients. [9] Ketamine a (NMDA antagonist)can cause hypertension and tachycardia when used intravenously. [10] We have compared epidural ketamine with dexmedetomidine to study the efficacy in prolonging the duration of analgesia and found that duration of analgesia was prolonged in group RD compared to group RK which was also supported by few other studies.…”
Section: Discussionmentioning
confidence: 99%